Correlation Between miR-223 Expression and Rheumatoid Arthritis - A, Angelika; Djohan, Carren Kwoknata; Julianto, Nadya Marcelina; Putri, Tiffanny Adora; Julietta, Vivi; Ratnasari, Nanda Risqia Pradana (Indonesia International Institute for Life Sciences, 2021)
Patients diagnosed with rheumatoid arthritis (RA) show symptoms of joint affiliations. Focusing on the epigenetic factors leading to RA, the expression of several miRNAs are assumed to be one of the components influencing the cause of RA. Consequently, the increased expression of miR-223 is hypothesized to be involved in the pathogenesis of RA. This study aims to analyze the increased expression of miR-223 of RA patients in comparison with the normal and healthy representatives. Five methods from five different studies were involved in this review. The RNA was first isolated from heparinized venous blood or peripheral blood of RA patients and healthy controls. Reverse transcription was done to convert isolated RNA into cDNA and the expression of miR-223 was then measured using real-time PCR. The expression of miR-223 had exhibited a considerable increase in its concentration on RA patients when compared to healthy controls. Besides, the heightened concentration is taken upon consideration as miR-223 has a role in the regulation of the immune system and inflammatory responses.